Impact of whale-watching vessels on humpback whale calling behavior on an Icelandic foraging ground during the Covid-19 pandemic - Laute, Amelie; Grove, Thomas J.; Rasmussen, Marianne H.; Smith, Adam; Loisa, Olli; Fournet, Michelle E.H. (Marine Ecology Progress Series, 2022)
Whale-watching vessels contribute to elevated ambient sound levels in marine habitats. The reduction in maritime tourism activities during the Covid-19 pandemic provided an unprecedented opportunity to study the acoustic response of marine mammals to noise associated with whale-watching activities. In this study, we used acoustic recordings, visual observations, and Automatic Identification System data to determine the changes in humpback whale Megaptera novaeangliae calling behavior associated with whale-watching vessels on a foraging ground in Skjálfandi Bay, Iceland. We compared pre-pandemic summer months (2018) with pandemic (2020) conditions to quantify reductions in vessel activity and determine changes in calling behavior. Broadband ambient sound pressure levels were low in both years (median ~90 dB RMS (25−1300 Hz) re 1 μPa). During the Covid-19 pandemic (2020), the number of whale-watching trips was reduced by 68.6%. The number of humpback whale call detections increased nearly 2-fold. Ambient sound pressure levels stayed the same. We found that humpback whales reduce their calling effort in the presence of vessel sound independent of the overall ambient sound. As whale-watching vessel traffic rebounds and continues to grow, demonstrating behavioral responses should inform management plans such as vessel codes of conduct and marine spatial planning.